Penguatan Kapasitas Kader Melalui Revitalisasi Posyandu dalam Upaya Peningkatan Layanan Kesehatan di Puskesmas Mutiara Kabupaten Asahan - Eva Dona Sinaga; Ali Imran Sirait; Marta Armita Silaban; Sella Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2025)
Posyandu, as a form of community-based health efforts, plays a crucial role in improving maternal and child health. However, its implementation in the Mutiara Community Health Center (Puskesmas Mutiara) in Asahan Regency still faces various challenges, such as low cadre capacity, suboptimal service quality, and limited community participation. This community service activity aims to strengthen cadre capacity through Posyandu revitalization as an effort to improve the quality of basic health services. A total of 63 Posyandu cadres participated in the activities, which were implemented through counseling, education, and coaching using revised service standard guidelines. This program was implemented through four stages: preparation, implementation, analysis of results, and evaluation. Improvement in cadre knowledge was measured using pretests and posttests. The results of the activity showed a significant increase in the level of knowledge of cadres, as seen in the change in assessment categories from the majority being in the